2005
DOI: 10.1007/s11010-005-4440-y
|View full text |Cite
|
Sign up to set email alerts
|

Okadaic acid induces tyrosine phosphorylation of IκBα that mediated by PKR pathway in human osteoblastic MG63 cells

Abstract: Treatment of human osteosarcoma cell line MG 63 cells with okadaic acid stimulated phosphorylation of IkappaBalpha, as judged from the results of Western blot analysis and a lambda protein phosphatase dephosphorylation assay. The stimulated phosphorylation of IkappaBalpha was both time- and dose-dependent. The phosphorylation sites of IkappaBalpha were taken to be tyrosine residues because the anti-phospho-tyrosine antibody bound to the samples immunoprecipitated with the anti-IkappaBalpha antibody. In the cel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
14
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
10

Relationship

6
4

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…In previous reports, we demonstrated that okadaic acid, an inhibitor of protein phosphatase types 1 and 2A, inhibited protein synthesis and stimulated phosphorylation of PKR and eIF-2a, and induced Runx2 protein in osteoblastic cells [32 -34]. However, okadaic acid did not phosphorylate eIF-2a in PKR-K/R mutant cells [34].…”
Section: Discussionmentioning
confidence: 75%
“…In previous reports, we demonstrated that okadaic acid, an inhibitor of protein phosphatase types 1 and 2A, inhibited protein synthesis and stimulated phosphorylation of PKR and eIF-2a, and induced Runx2 protein in osteoblastic cells [32 -34]. However, okadaic acid did not phosphorylate eIF-2a in PKR-K/R mutant cells [34].…”
Section: Discussionmentioning
confidence: 75%
“…IκBα was degraded upon OA treatment in MG63 cells. We previously demonstrated that IκBα was phosphorylated on tyrosine residues by the OA-treatment (36). In the present study IκBα was phosphorylated at least on serine residues at 32 position, because the anti-phospho IκBα (Ser32) recognized the phosphorylated form of IκBα.…”
Section: Discussionmentioning
confidence: 99%
“…Osteoblast differentiation and calcification through modulation of STAT1␣ and/or Runx2 expression by PKR has been also described (249).…”
Section: Pkr Control Of Cell Differentiationmentioning
confidence: 99%